Biology and Population Dynamics of Sacramento Splittail (Pogonichthys macrolepidotus) in the San Francisco Estuary: A Review - Peter B Moyle; Randall D Baxter; Ted Sommer; Ted C Foin; Scott A Matern (San Francisco Estuary and Watershed Science, 2004)
The Sacramento splittail (Pogonichthys macrolepidotus) is a cyprinid fish endemic to the Central Valley of California with a range that centers on the San Francisco Estuary. It is a state Species of Special Concern and was only recently (2003) delisted as a threatened species by the U. S. Fish and Wildlife Service. Splittail live 7-9 years, tolerate a wide range of environmental conditions, and have high fecundity. Typically, adults migrate upstream in January and February and spawn on seasonally inundated floodplains in March and April. In May the juveniles migrate back downstream to shallow, brackish water rearing grounds, where they feed on detritus and invertebrates for 1-2 years before migrating back upstream to spawn. Seven long-term sampling programs in the estuary indicate that the splittail population is maintained by strong year classes resulting from successful spawning in wet years, although some spawning occurs in all years. Modeling shows them to be resilient, but managing floodplains to promote frequent successful spawning is needed to keep them abundant. Additionally, it is important to provide safe migration corridors between spawning and rearing grounds as well as abundant high-quality brackish water rearing habitat. Key research needs are (1) to examine how the timing, magnitude, and duration of high flows contribute to the generation of strong year classes, (2) to describe differences in young of year survival on the floodplain and in river margins from hatching to down-river migration, (3) explore the possible trophic effects of new invaders such as the overbite clam and Siberian prawn, and (4) determine the response of splittail populations to climate change and sea level rise.